Mothers’ Experience In Support Of Exclusive Breastfeeding: Scoping Review: Pengalaman Ibu Bekerja Mendapatkan Dukungan Dalam Pemberian Asi Eksklusif : Scoping Review - Nurvitriana, Nidya Comdeca; Triratnawati, Atik; Warsiti (Jurnal Kebidanan Midwiferia, 2020)
Exclusive breastfeeding is one of the important strategies to reduce child mortality which has been recommended by the World Health Organization (WHO). Exclusive breastfeeding is defined as the provision of nutritional intake to infants from the first time of birth until at least 6 months can without additional food and drinks. In 2016 WHO showed that the average level of breastfeeding worldwide was only 38% which occurred in urban areas. In the city area it was found that many breastfeeding mothers worked and obstacles and support arose. Working mothers have low trust and intention so as to increase the frequency of failure to give exclusive breastfeeding. This study aims to review support for exclusive breastfeeding. The systematic literature review covers eight stages, namely: Identifying middle frequency problems, Determining priority problems and research questions, Inclusion and Exclusion Criteria, literature search, Selecting articles, data extraction, Critical Assessment, Data collection and Mapping. Data searched from Pubmed and Onesearch. The researchers, then, examined the feasibility of finding documents. Finally, researchers found 9 documents that research criteria. Information on exclusive breastfeeding support was found from 5 journals, namely internal factors (self, family), while external factors (health workers, work environment) were found from 5 journals from 9 journals. The highest influence of support was a work environment characterized by a lack of support from facilities, coworkers, workloads of institutions that influenced the mothers' own intentions. The mother's experience of getting support from exclusive breastfeeding includes internal (self, family) and external (health worker, work environment).